Assessment of vitamin D status and vitamin D receptor polymorphism in Egyptian children with Type 1 diabetes - Eman A. Mostafa; Maha M.A. Abo Hashish; Nagwa Abdallah Ismail; Hasanin M. Hasanin; Rasha M. Hasanin; Aliaa Ahmed Wahby; Ingy Ashmawy; Shereen Hamdy Abd El Aziz; Mai Magdy Abdel Wahed (Journal of Genetic Engineering and Biotechnology, 2024)
Background: The endocrine system of vitamin D regulates about 3 % of the human genome. Vitamin D exerts its actions via a nuclear vitamin D receptor (VDR) which in turn regulates insulin secretion from the pancreas. VDR gene polymorphisms could have an impact on how autoimmune illnesses like Type 1 diabetes mellitus (T1DM) develop. We aimed to explore the relation between T1DM and VDR gene polymorphisms in Egyptian diabetic children and their siblings. Methods: Enzyme-linked immunosorbent assay was used to quantify 25(OH) vitamin D in the study, which had 179 participants (group 1 = 85 diabetic children, group 2 = 57 siblings of the patients, group 3 = 37 healthy controls). Real-time polymerase chain reaction (RT-PCR) was used to analyze the genotyping of the VDR gene polymorphisms Apa-I (rs7975232), Fok-I (rs2228570), Taq-I (rs731236) and Bsm-I (rs1544410). Results: The mean serum 25(OH) vitamin D levels was significantly lower in T1DM patients (14.99 ± 9.24 ng/mL) and siblings (16.31 ± 7.96 ng/mL) compared to the controls (19.48 ± 7.42 ng/mL) (p = 0.031). The genotypes distribution of VDR Fok-I (rs2228570) and Bsm-I (rs1544410) polymorphisms showed a significant difference between patients, siblings and controls as P = 0.001 and 0.026 respectively, while the VDR ApaI and TaqI polymorphisms did not. FokI-A allele frequency was significantly lower in T1DM patients and siblings than in controls (p < 0.001). FokI-AA genotype had a statistical significant higher vitamin D levels than other genotypes with p value of 0.024. Conclusion: Our study found that T1DM children had lower vitamin D levels, and VDR FokI and BsmI gene polymorphisms were linked to T1DM in Egyptian children. Determining the relationship between vitamin D levels and VDR polymorphisms, particularly the FokI and other genetic analyses may aid in the early diagnosis of T1DM in children.